MURABAHAH TRANSACTION IN SHARIA BANK WITH WORK POTENTIALLY INFRINGE THE SYARIAH ECONOMIC LAW - minanul azis (Jurnal Pembaharuan Hukum, 2017)
Islamic bank generally deputes customers to buy product for supplier in terms of deferred payment sale purchase agreement, there are possibilities: an agreement upon the delivery of money, and customers are not in accordance with bank in spending money. The agreement of deferred payment sale is appropriate with the advisory opinion of National Sharia Board, goods officially become the property of bank. The customers are generally not in accordance with bank in spending money, so that the value are often not in accordance with the price of bank within the agreement, it can be concluded based on advisory opinion of National Sharia Board that deferred payment sale is invalid.